Imagining windmills : trust, truth and the unknown in the arts therapies - Hougham, Richard; Lp̤ez F. Cao, Mariǹ; Scoble, Sarah (Routledge, 2022)
"Imagining Windmills presents a compilation of scholarly chapters by selected authors of global standing in the arts therapies. This book reflects the theme of the 15th International Conference of the European Consortium for Arts Therapies (ECArTE), held in Alcal ̀de Henares, Spain, birthplace of Miguel de Cervantes. This innovative work seeks to further understanding of arts therapy education, practice and research and incorporates current thinking from art therapists, dance-movement therapists, dramatherapists and music therapists. Writers from Belgium, Germany, Greece, India, Israel, Italy, The Netherlands, Spain, Sweden, UK, and USA combine to give an international voice to the book, which celebrates cultural distinctiveness, while also presenting shared intercultural developments in the professions. This interdisciplinary publication explores questions of the unknown and the imagined, misconception, delusion, truth, and trust in the arts therapies. It enquires into ways in which education and the practice of the arts therapies engage with the imagination as a place of multiple realities, which may lead us closer to finding our truth. This book will be of interest and relevance not only to those in the arts therapeutic community, but also to a broad audience including those in related professions - for instance psychology, sociology, the arts, medicine, health and wellbeing and education"--